Developing High-Quality Horticultural Products With Network Culture and Marketing Potential in Reducing Food Loss and Waste - Fakhiroh, Siti Zakiyatul; Amanda, Sifa Saskia; Nuraida, Dhita; Sinaga, Hanif Zaidan; Hoirunnisa, Siti Mega Sania (INOVATOR, 2024)
The agricultural sector faces challenges in meeting the demand for high quality Horticultural products as the world population grows. Tissue Culture techniques involve growing plants in a controlled environment, offering an innovative solution to increase agricultural production. This research explores the commercial opportunities and appropriate marketing strategies in developing high-quality agricultural products through tissue culture, as well as analyzing its role in addressing food loss and wastage. Through a literature review and questionnaires, this study shows that the use of superior tissue-cultured seeds, the application of proper cultivation techniques, and good post-harvest handling can produce high-quality horticultural products. Effective marketing, such as the use of digital technology and market analysis, plays an important role in marketing these products. In addition, proper sterilization and technical manipulation in tissue culture can reduce contamination and seedling loss, thus contributing to addressing Food Loss and Waste. This research provides valuable insights for the development of high-quality horticultural products through tissue culture, as well as the implementation of marketing strategies and agricultural practices that support global food security. In addition, tissue culture techniques that involve sterilization and proper technical manipulation can reduce contamination and seed loss, thereby contributing to overcoming the problem of food loss and waste. Overall, this study provides insights into how to develop high-quality agricultural products and effective marketing strategies, especially by leveraging digital technology to sell products online in order to reduce food loss and maximize profits. Thus, the development of high-quality horticultural products through tissue culture can support global food security.